An integrated vendor–buyer supply chain model for backorder price discount and price-dependent demand using service level constraints and carbon emission cost. Issue 1 (2nd January 2022) - Malleeswaran, B.; Uthayakumar, R.
Abstract : This paper derives a single-vendor single-buyer supply chain model with setup cost reduction, controllable lead time and backorder price discounts using service level constraints. The customer's demand is assumed to be selling-price dependent and the lead time demand follows a normal distribution. This integrated model is used to optimise the total number of shipments, order quantity, safety factor, setup cost and backorder price discount. An algorithm is developed to obtain the numerical results and to demonstrate the applications and performance of the proposed methodology.